OBSERVATIOfJS ON THE DEVELOPMENTAL STAGES OF THE SMOOTH DCiGFISH, ERIDACNIS RADCLIFFEI SMITH FROM GULF OF MANNAR - Nair, R V; Appukkuttan, K K (Indian Journal of Fisheries, 2011)
The structure of mature reproductive organs of fifteien adult females of Eridacn’.s radcliffei. ranging in total length from 150 to 218 mm collected from the trawl catches off Mandapam in Gulf of Mannar during February, 1972 at a depth ranging frori 100 to 150 fathoms were studied and the various stages of intra-uterine embryos are described and discussed. A close examination of different stages of embryos revealed that this species exhibits ovoviviparous type of development. The intra-uterine egg is enclosed in a thin shell membrane which disappears when the embryo develops inside the uterus. The embryos are seen free inside the uterus and no placental connection has been observed in any stage of development.